Hubungan antara fear of marriage dengan intention to marry pada perempuan generasi Z. - Putri Cinta Maulida Fahsa; Yuarini Wahyu Pertiwi; Wahyu Aulizalsini Alurmei (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the relationship between fear of marriage and intention to marry in Generation Z women in Bekasi City. Ambivalence toward marriage — characterized by the coexistence of strong marital intentions and pronounced fears — has become increasingly prevalent among this cohort. A quantitative correlational design was employed with 100 Generation Z women aged 14–29 years recruited through purposive sampling. Fear of marriage was measured using a modified Spanish ECR-12 (González et al., 2020), and intention to marry was assessed using a TPB-based scale (Xie Hong, 2022). Pearson product-moment correlation analysis in JASP (v. 0.97.1) revealed a statistically significant positive relationship (r = 0.373, p .001), indicating that stronger marital intention is associated with greater anticipatory fears about marriage.